(untitled) (Interdisciplinary Research in Education, 2022)
Recent trends of mathematics education using the open and distance mode was more effective recent and useful. The theoretical framework was the full of the paradigm shift of the recent mode and relevant of the system. I have taught in the Operations Research in the online education and make the effective idea of the education. The pedagogy of the education in the methodology, groups of students in the schools. The different mode of student was the mode of mathematics in the Game theory, Markov chains, Queuing theory, Dynamic programming, Transportation and Assessment programs. Inventory and Replacement model and Forecasting model are the beautiful aspect in the methods. The online methods were the better for the books. The online methods were the virtual classroom, online conceptual elaboration and technology integrated pedagogy in open and distance learning (ODL). It is suggested that LMS like Moodle is more effective in teaching and learning mathematics education using open and distance mode for higher education in Nepal.